MORPHOMETRY OF GASTRIC WALL LAYERS UNDER THE INFLUENCE OF PALM OIL - Ro‘zibek T. Tolmasov; Utkir M. Mirsharapov (Central Asian Journal of Medicine, 2025)
Obesity is currently one of the most common chronic diseases in the world. It should be noted that nutrition accounts for 97% of all forms of obesity. This is largely due to changes in daily nutrition and lifestyle. The relevance of this problem is due to the fact that obesity is the main factor and is associated with metabolic diseases. It significantly increases the risk of developing many diseases and pathological processes To develop prevention of gastric diseases and increase the possibility of reducing disease complications by comparative morphometric analysis of the structure of the mucous, submucosal, muscular and serous membranes of the gastric wall of rats fed palm oil, comparative analysis of the density of mucous glands, and evaluation and comparison of their morpho-functional changes under experimental conditions.